Iron-based nano-enzyme and application thereof in detection of quinolone antibiotics
By preparing iron-based nanoenzymes with nanoprismatic mesoporous structures, the problems of high efficiency and cost of traditional quinolones antibiotic detection methods are solved, and visual detection of high sensitivity, low detection limit and wide linear response range of norfloxacin is achieved.
Patent Information
- Application Number
- CN202510068114.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-16
- Publication Date
- 2025-04-15
- Estimated Expiration
- 2045-01-16
AI Technical Summary
Traditional quinolone antibiotic detection methods have long incubation time, complex electrode preparation processes or require expensive equipment, resulting in high detection efficiency and cost.
By using the preparation method of iron-based nanoenzyme, Ce/Fe-P nanoenzyme was prepared by mixing ferric chloride hexahydrate and cerium nitrate hexahydrate in water, then reflux reaction with the organic polyacid ligand solution, and then calcined with sodium hypophosphite under a nitrogen atmosphere, Ce/Fe-P nanoenzyme was prepared and tested on the basis of this.
This method improves the contact area and active sites with the substrate by preparing 0.5-Ce/Fe-P nanoenzymes with nanoprismatic mesoporous structures, enhances the ability to catalyze oxidation reactions, and realizes visual detection of high sensitivity, low detection limit and wide linear response range for norfloxacin.
Smart Images

Figure CN119819336A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of pollutant detection, and relates to an iron-based nanozyme and an application thereof in the detection of quinolone antibiotics. Background Art
[0002] Antibiotics, as a class of drugs, can both kill bacteria and inhibit their growth and reproduction to treat infections caused by bacteria. Among them, norfloxacin (NOR) has high antibacterial activity against aerobic Gram-negative bacteria. Due to its antibacterial properties, NOR plays an important role in the treatment of urinary tract infections, prostatitis, intestinal infections, and infections caused by skin-sensitive bacteria. However, long-term use of NOR can cause bacterial resistance and allergic reactions, which may pose a serious risk to human health. Therefore, the detection of NOR residues in water bodies such as rivers and lakes is of great significance. So far, scientists have developed a variety of methods to determine NOR, including cyclic voltammetry, fluorescence spectroscopy, high-performance liquid chromatography, and enzyme-linked immunosorbent assay. However, these methods usually require long incubation times, complex electrode preparation processes, or expensive equipment. Summary of the invention
[0003] Aiming at the problems existing in the traditional quinolone antibiotic detection, the present invention proposes a novel iron-based nanozyme and its application in the quinolone antibiotic detection.
[0004] In order to achieve the above object, the present invention is implemented by adopting the following technical solutions: A method for preparing an iron-based nanozyme, comprising the following steps: Step (1): adding ferric chloride hexahydrate and cerium nitrate hexahydrate into water and mixing them evenly to obtain a mixed solution A, mixing the mixed solution A evenly with an organic polyacid ligand solution, and then performing a reflux reaction to obtain a Ce / Fe-MOF precursor.
[0005] Step (2): Add Ce / Fe-MOF precursor and sodium hypophosphite into a tube furnace and calcine under nitrogen atmosphere to obtain Ce / Fe-P.
[0006] Preferably, the organic polyacid in step (1) is fumaric acid, and the molar ratio of ferric chloride hexahydrate to fumaric acid is 1:1; the molar ratio of cerium nitrate hexahydrate to ferric chloride hexahydrate is 1:1-30, preferably 1:6.
[0007] Preferably, in step (1), the reflux reaction temperature is 90-110° C., and the reflux reaction time is 3-5 h.
[0008] Preferably, the calcination temperature in step (2) is 330-360° C., and the calcination holding time is 2-5 h.
[0009] The present invention proposes the use of the iron-based nanozyme prepared by the above method in the detection of quinolone antibiotics, wherein the quinolone antibiotics are norfloxacin, enrofloxacin and ciprofloxacin.
[0010] The application method is: iron-based nanozyme, TMB, H 2 O 2 , quinolone antibiotics and NaAc-HAc buffer were evenly mixed to obtain a reaction system, and the reaction was allowed to stand naturally for at least 5 minutes, filtered, and then the absorbance at 652 nm was recorded using a UV-visible spectrophotometer.
[0011] Preferably, the pH of the NaAc-HAc buffer is 3.0, the volume fraction of the NaAc-HAc buffer in the reaction system is 75-80%, and during detection, the TMB concentration is preferably 0.5 mmol / L, and H 2 O 2 The preferred concentration is 0.5 mmol / L.
[0012] Compared with the prior art, the advantages and positive effects of the present invention are: 1. The 0.5-Ce / Fe-P material synthesized in the present invention has a nano-prism mesoporous structure, which effectively increases the contact area with the substrate and provides more active sites. 2 O 3 Phase transformation to γ-Fe 2 O 3 In addition, the introduction of an appropriate amount of Ce doping effectively improves the charge transfer rate, which is more conducive to the catalytic oxidation reaction of the nanozyme.
[0013] 2. The raw materials are cheap and abundant in resources, the synthesis cost is low, and the product performance is stable, which is suitable for mass synthesis.
[0014] 3. Based on the principle that low concentration of NOR enhances the activity of 0.5-Ce / Fe-P, while high concentration inhibits the activity of 0.5-Ce / Fe-P, visual detection of NOR can be achieved with high sensitivity, low detection limit (0.78nM), wide linear response range (50nM-2.5μM and 200 μM-650μM), good selectivity and stability. BRIEF DESCRIPTION OF THE DRAWINGS
[0015] Figure 1 A is the X-ray diffraction pattern of Ce / Fe-MOF, Figure 1 B is the X-ray diffraction pattern of 0.5-Ce / Fe-P nanozyme.
[0016] Figure 2 A is the SEM image of Ce / Fe-MOF. Figure 2 B is the TEM image of Ce / Fe-MOF. Figure 2 C is the SEM image of 0.5-Ce / Fe-P, Figure 2 D is the TEM image of 0.5-Ce / Fe-P.
[0017] Figure 3 This is the high-resolution transmission electron microscopy (HRTEM) image of 0.5-Ce / Fe-P.
[0018] Figure 4 N of 0.5-Ce / Fe-P 2 Adsorption analytical isotherms (inset: corresponding pore size distribution curves).
[0019] Figure 5 A comparison chart of the POD-like activities of different nanozymes.
[0020] Figure 6 This is the specific detection diagram of 0.5-Ce / Fe-P nanozyme.
[0021] Figure 7 This is a graph showing the effect of the pH value of the buffer solution on the activity of 0.5-Ce / Fe-P nanozyme. DETAILED DESCRIPTION
[0022] In order to more clearly understand the above-mentioned purpose, features and advantages of the present invention, the present invention is further described below in conjunction with specific embodiments. It should be noted that the embodiments of the present application and the features in the embodiments can be combined with each other without conflict.
[0023] In the following description, many specific details are set forth to facilitate a full understanding of the present invention. However, the present invention may also be implemented in other ways than those described herein. Therefore, the present invention is not limited to the specific embodiments of the following disclosure.
[0024] Example 1 Add 3 mmol FeCl in 30 mL deionized water 3 6H 2 O and 0.5mmol Ce(NO 3 ) 3 6H 2 O, and 3mmol of fumaric acid was dissolved in 30mL of deionized water. The two solutions were ultrasonicated for 5min and then mixed, stirred at room temperature for 30min, and the stirring rate was 200rpm. The obtained mixture was refluxed in an oil bath at 100℃ for 4h. After the reaction, ethanol and deionized water were alternately centrifuged and washed 3 times, the centrifugal rate was 9000rmp, and the centrifugal time was 5min each time. Then, a yellow-brown solid (0.5-Ce / Fe-MOF precursor) was obtained after drying at 60℃ for 12h.
[0025] 200 mg of sodium hypophosphite was placed upstream of the tube furnace, and 50 mg of the 0.5-Ce / Fe-MOF precursor prepared above was placed downstream. Nitrogen was introduced at a rate of 10 m / s. 3 / h, after the air in the tube furnace was exhausted for 5 minutes, the temperature of the tube furnace was raised to 350°C, the heating rate was 2°C / min, and the temperature was kept for 5 hours. During the calcination process, sodium hypophosphite was decomposed and contacted with the downstream precursor under the action of nitrogen flow to undergo phosphating reaction. After the calcination was completed, it was naturally cooled to room temperature to obtain a black solid, which was recorded as 0.5-Ce / Fe-P.
[0026] The prepared 0.5-Ce / Fe-MOF precursor and 0.5-Ce / Fe-P were characterized by XRD. The results are as follows Figure 1 As shown in A and 1B. Figure 1 It can be seen that the crystal form of 0.5-Ce / Fe-MOF material does not change significantly after Ce doping; the crystal form of 0.5-Ce / Fe-P material mainly includes γ-Fe 2 O 3 and Fe 7 (PO 4 ) 6 .
[0027] The prepared 0.5-Ce / Fe-MOF precursor and 0.5-Ce / Fe-P material were characterized by SEM and TEM. Figure 2 As shown in A-2D. Figure 2 A and 2B show that 0.5-Ce / Fe-MOF is a solid rod-like structure with a smooth surface; Figure 2 C and 2D show that the 0.5-Ce / Fe-P material produced after phosphating has a porous structure, the surface roughness of the material increases, and many nanoparticles are attached.
[0028] The lattice state of 0.5-Ce / Fe-P material is as follows Figure 3 , Figure 3 The lattice spacing of 0.30 nm is Fe 7 (PO 4 ) 6 The (210) plane of the γ-Fe 2 O 3 (112) and (4012) crystal planes.
[0029] N of 0.5-Ce / Fe-P material 2 The adsorption-desorption curve is Figure 4 As shown in the figure, the curve has a significant hysteresis loop. From the characterization results, 0.5-Ce / Fe-P has a 23.7 m 2 / g high specific surface area and a mesoporous structure on the surface. The mesoporous nature of the nanozyme is conducive to the contact between the substrate and the material. The large contact area between the two materials can provide more active sites, which is conducive to enhancing the catalytic oxidation performance of the material.
[0030] Example 2 The examples are consistent with those in Example 1 unless otherwise specified. 10 mmol FeCl 3 6H 2 O and 0.5mmol Ce(NO 3 ) 3 6H 2 O, and 10mmol of fumaric acid was dissolved in 30mL of deionized water. The two solutions were ultrasonicated for 5min and then mixed, stirred at room temperature for 30min, and the stirring rate was 200rpm. The obtained mixed solution was refluxed in a 95℃ oil bath for 4.5h. After the reaction, it was washed alternately with ethanol and water and centrifuged 3 times, the centrifugal rate was 9000rmp, and the centrifugal time was 5min each time, and then dried at 60℃ for 12h to obtain a yellow-brown solid.
[0031] 200 mg of sodium hypophosphite was placed upstream of the tubular furnace, and 50 mg of the precursor prepared above was placed downstream. After nitrogen was introduced to replace the air, the temperature of the tubular furnace was raised to 330°C at a heating rate of 2°C / min and kept warm for 4 hours. After calcination, it was naturally cooled to room temperature to obtain a black solid iron-based nanozyme.
[0032] Example 3 The examples are consistent with those in Example 1 unless otherwise specified. 15 mmol FeCl was added to 30 mL of deionized water. 3 6H 2 O and 0.5mmol Ce(NO 3 ) 3 6H 2 O, and 15mmol of fumaric acid was dissolved in 30mL of deionized water. The two solutions were ultrasonicated for 5min and then mixed, stirred at room temperature for 30min, and the stirring rate was 200rpm. The obtained mixed solution was refluxed in a 110℃ oil bath for 4.5h. After the reaction, it was washed alternately with ethanol and water and centrifuged 3 times, the centrifugal rate was 9000rmp, and the centrifugal time was 5min each time, and then dried at 60℃ for 12h to obtain a yellow-brown solid.
[0033] 200 mg of sodium hypophosphite was placed upstream of the tubular furnace, and 50 mg of the precursor prepared above was placed downstream. After nitrogen was introduced to replace the air, the temperature of the tubular furnace was raised to 360°C at a heating rate of 2°C / min and kept warm for 2 hours. After calcination, it was naturally cooled to room temperature to obtain a black solid iron-based nanozyme.
[0034] The iron-based nanozyme prepared in Example 1 was used for performance testing.
[0035] 1. Determination of POD-like activity of iron-based nanozymes The 0.5-Ce / Fe-P nanozyme prepared in Example 1 was added to ethanol to prepare a dispersion with a concentration of 100 μg / mL. 50 μL TMB (3,3',5,5'-tetramethylphenylthiazole disulfonate, CAS No.: 54827-18-8) and 50 μL H 2 O 2 Then 100 μL of the dispersion was added, and the mixture was reacted at room temperature for 5 min. The filtrate was then filtered and tested with a UV-visible spectrophotometer, and the UV-visible absorption spectrum at 652 nm was recorded. Figure 5 C, by Figure 5 C shows that 0.5-Ce / Fe-P nanozyme has excellent POD-like activity.
[0036] 2. Standard curve determination The detection was performed by changing the concentration and volume of norfloxacin (NOR, purchased from Sigma-Aldrich), while keeping TMB and H 2 O 2 The added volume was 50 μL, and the total volume of the system was 1 ml with NaAc-HAc buffer solution of pH 3.0. After reaction and filtration, the UV-visible absorption spectrum at 652 nm was tested to test the detection linear range of 0.5-Ce / Fe-P nanozyme. After testing, there was a good linear relationship between NOR concentration and absorbance in the range of 50nM-2.5μM and 200-650μM, and the detection limit was 0.78 nM. Among them, in the concentration range of 50nM-2.5μM, y=0.46x+1.57, R 2 =0.980; y=0.0020x+1.46 in the range of 200-650μM, R 2 =0.984, x is NOR concentration, y is absorbance.
[0037] 3. Specificity test Detection of Na + 、Ni 2+ , Mn 2+ , K + , Ca 2+ 、Cd 2+ , Cl -, glycine (Gly), sugars (glucose Glu, fructose Fru, maltose Mal) and other antibiotics (CIP, ENR) interfere with the test results. The interfering ions are provided by the following substances: ciprofloxacin (CIP), sodium chloride (Cl - 、Na + ), manganese chloride (Mn 2+ ) was purchased from China MacLean Biochemical Technology Co., Ltd. Potassium chloride (K + ), nickel acetate tetrahydrate (Ni 2+ ), cadmium chloride (Cd 2+ ) was purchased from Sinopharm Chemical Reagent Co., Ltd. D-fructose and maltose were purchased from China Huixing Biochemical Reagent Co., Ltd. Calcium chloride (Ca 2+ ) was purchased from Myrel, glucose was purchased from Beijing Zhuangmeng International Biotechnology Co., Ltd., enrofloxacin (ENR) was purchased from Aladdin, and glycine (Gly) was purchased from Sinopharm Chemical Reagent Co., Ltd. The specific operation is as follows: weigh the above-mentioned substances or sugars that provide interfering ions and add them to 10ml of deionized water respectively to prepare different interfering solutions with the concentration of each interfering ion reaching 0.26mol / L and the antibiotic CIP and ENR reaching 13mmol / L. The 0.5-Ce / Fe-P nanozyme prepared in Example 1 was added to ethanol to prepare a dispersion with a concentration of 100 μg / mL, and then 100μL of the dispersion was added to 50μL TMB, 50μL H 2 O 2 , 50μL interfering solution and 750μL NaAc-HAc buffer solution (pH 3.0). The reaction was allowed to react at room temperature for 5 min, then filtered. The filtrate was detected by UV-visible spectrophotometer and the UV-visible absorption spectrum at 652nm was recorded. The results are shown in Figure 6 Only after adding other antibiotics, the POD-like activity of 0.5-Ce / Fe-P had the same effect as NOR.
[0038] 4. Real sample testing The standard addition method was used to detect the detection of NOR by 0.5-Ce / Fe-P in actual water samples. The specific operation was as follows: tap water from the Chemistry Building of Nanjing Tech University and Wahaha purified water were taken for real sample detection. The experiment used the standard addition method to add different concentrations of NOR to each water sample, and 50 μL of water samples were taken for detection. The actual content of NOR in the water samples of each test group is shown in Table 1. The 0.5-Ce / Fe-P nanozyme prepared in Example 1 was added to ethanol to prepare a dispersion with a concentration of 100 μg / mL. Then 100 μL of the dispersion was added to a 50 μL TMB, 50 μL H 2 O 2, 50μL water sample in 750μL NaAc-HAc buffer solution (pH 3.0), react naturally at room temperature for 5 min, then filter, the filtrate is detected by UV-visible spectrophotometer, and the UV-visible absorption spectrum at 652nm is recorded, and repeated three times. Substitute into the working curve and calculate the detection amount. The results are shown in Table 1. The results in Table 1 show that the relative standard deviation of the detection value is ≤3.75% (n = 3), indicating that the colorimetric sensor has good repeatability in the rapid detection of NOR content in water. In addition, the recovery rate is between 98.6-106.8%, which proves that this method has good accuracy and reliability for the determination of NOR in actual water samples.
[0039] Table 1 Test results of real samples Comparative Example 1 Without adding cerium nitrate hexahydrate, the rest of the preparation process was the same as in Example 1. The prepared nanozyme was recorded as Fe-P nanozyme, which was added to ethanol to prepare a dispersion with a concentration of 100 μg / mL. Then, 100 μL of the dispersion was added to a 50 μL TMB, 50 μL H 2 O 2 The mixture was added to 800 μL NaAc-HAc buffer solution (pH 3.0) and reacted at room temperature for 5 min. The filtrate was then filtered and the filtrate was detected by UV-visible spectrophotometer and the UV-visible absorption spectrum at 652 nm was recorded. Figure 5 B. 50 μL TMB, 50 μL H 2 O 2 The test results after the same treatment process of 900μL NaAc-HAc buffer solution (pH 3.0) were compared. Figure 5 A, by Figure 5 B shows that the POD activity of the Fe-P nanozyme prepared in this comparative example is not as high as that of the 0.5-Ce / Fe-P nanozyme prepared in Example 1.
[0040] Comparative Example 2 The difference between this comparative example and Example 1 is that the pH of the buffer solution is different. The pH values of the buffer solution are replaced with NaAc-HAc buffer solutions of 2, 4, 5, 6, 7, and 8, respectively. The other conditions are consistent with those of Example 1. The samples are treated in the same steps as the POD-like activity assay of the iron-based nanozyme, and the UV-visible absorption spectrum at 652 nm is recorded. The results are as follows: Figure 7 As shown. Figure 7 It can be seen that the absorbance value is the highest when the buffer pH is 3.0.
[0041] The above description is only a preferred embodiment of the present invention and does not limit the present invention in other forms. Any technician familiar with the profession may use the technical content disclosed above to change or modify it into an equivalent embodiment with equivalent changes and apply it to other fields. However, any simple modification, equivalent change and modification made to the above embodiment based on the technical essence of the present invention without departing from the content of the technical solution of the present invention still falls within the protection scope of the technical solution of the present invention.
Claims
1. A method for preparing an iron-based nanozyme, characterized in that: Here are the steps: Step (1): adding ferric chloride hexahydrate and cerium nitrate hexahydrate into water and mixing them evenly to obtain a mixed solution A, mixing the mixed solution A evenly with an organic polyacid ligand solution, and then performing a reflux reaction to obtain a Ce / Fe-MOF precursor; Step (2): Add Ce / Fe-MOF precursor and sodium hypophosphite into a tube furnace and calcine under nitrogen atmosphere to obtain Ce / Fe-P.
2. The method for preparing the iron-based nanozyme according to claim 1, characterized in that: The organic polyacid in step (1) is fumaric acid, and the molar ratio of ferric chloride hexahydrate to fumaric acid is 1:1; the molar ratio of cerium nitrate hexahydrate to ferric chloride hexahydrate is 1:1-30.
3. The method for preparing the iron-based nanozyme according to claim 1, characterized in that: In step (1), the reflux reaction temperature is 90-110° C., and the reflux reaction time is 3-5 h.
4. The method for preparing the iron-based nanozyme according to claim 1, characterized in that: In step (2), the calcination temperature is 330-360° C. and the calcination time is 2-5 h.
5. Application of the iron-based nanozyme prepared by any one of the methods of claims 1-4 in the detection of quinolone antibiotics.
6. The use according to claim 5, characterized in that: The application method is: the iron-based nanozyme, TMB, H2O2, quinolone antibiotics and NaAc-HAc buffer are mixed evenly to obtain a reaction system, the system is allowed to react naturally for at least 5 minutes, filtered, and then the absorbance value at 652 nm is recorded using a UV-visible spectrophotometer.
7. The use according to claim 6, characterized in that: The pH of the NaAc-Hac buffer solution is 3.0, and the volume fraction of the NaAc-HAc buffer solution in the reaction system is 75-80%.
Citation Information
Patent Citations
Composite material nano enzyme as well as preparation method and application thereof
CN114100586A
Bimetal MOF (Metal Organic Framework) nano-enzyme as well as preparation method and application thereof
CN116789978A
Iron nano-enzyme, preparation method thereof and application of iron nano-enzyme in rapid detection of norfloxacin
CN118268037A
MOF (Metal Organic Framework) nano-enzyme, synthesis method and method for detecting fluorine ions by using MOF nano-enzyme
CN118655128A
Microbial self-phosphorization synthesis method of anion-cation double-defect nickel phosphide nano-enzyme
CN118950056A
Cited By
Quinolone antibiotic automatic monitor and automatic monitoring method
CN121830546A
Oxygen-vacancy-rich iron oxide nano-enzyme, preparation method thereof and application of oxygen-vacancy-rich iron oxide nano-enzyme in cystatin C detection
CN122399810A
An oxygen-enriched vacancy iron oxide nanozyme, its preparation method, and its application in cystatin C detection.
CN122399810B